Enti religiosi e riforma del Terzo settore: verso nuove partizioni nella disciplina degli enti religiosi (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. Gli enti religiosi nelle leggi speciali sul non profit. Le presenze e le assenze consolidate - 3. Gli enti religiosi nella riforma del Terzo settore. Le nuove assenze - 4. Gli “enti religiosi civilmente riconosciuti”, i loro rami sociali e gli assestamenti nella disciplina degli enti religiosi.Religious Organizations and Third Sector Reform Act: new distinctions among Religious OrganizationsABSTRACT: This essay recalls the intertwining between religious organizations and third sector organizations hitherto well-established in Italian law. Then it examines the Third Sector Reform Act recently approved in Italy, which in its turn subjects religious organizations, under certain terms, to third sector regulations. The essay focuses on the fresh distinctions introduced by the said Reform among various types of religious organizations and underlines the new, consequent discrepancies in the overall regulation of these organizations.
Keywords: Enti religiosi